Evaluation of the Value Added Cream Cheese Production in Samarinda - Cori Qamara; Amalina Nur Wahyuningtyas; I Putu Gede Didik Widiarta; Novemia Fatmarischa (International Journal of Business, Marketing, Economics & Leadership (IJBMEL), 2026)
There are chances for small and medium-sized businesses (SMEs) to boost local agricultural economies and increase profitability due to the rising demand for value-added dairy products.  This study uses the Hayami approach to evaluate the value distribution along the production chain in order to investigate the economic potential of cream cheese production in Samarinda, Indonesia.  In-depth producer interviews, cost documentation, questionnaires, and production process observations were used to gather primary data.  Identifying the main cost components and evaluating value generation at the processing step were the main objectives of the investigation.  The results show that processing adds a substantial amount to the total product value, with the acquisition of raw materials and packaging being the main sources of expense. Maximizing by-products like whey, implementing cost-effective packaging, and optimizing input sourcing are all ways to boost profitability. According to the report, local cream cheese makers can become more resilient and competitive by focusing on specialized markets, improving branding, and fortifying supply chain integration. These observations serve as the foundation for business plans and regulatory suggestions meant to promote long-term expansion in the artisanal dairy industry.